Education and Development in Colonial and Postcolonial Africa Policies, Paradigms, and Entanglements, 1890s-1980s - Matasci, Damiano; Jerónimo, Miguel Bandeira; Dores, Hugo Gonçalves (Global Histories of Education, 2020)
This open access edited volume offers an analysis of the entangled histories of education and development in twentieth-century Africa. It deals with the plurality of actors that competed and collaborated to formulate educational and developmental paradigms and projects: debating their utility and purpose, pondering their necessity and risk, and evaluating their intended and unintended consequences in colonial and postcolonial moments. Since the late nineteenth century, the "educability" of the native was the subject of several debates and experiments: numerous voices, arguments, and agendas emerged, involving multiple institutions and experts, governmental and non-governmental, religious and laic, operating from the corridors of international organizations to the towns and rural villages of Africa. This plurality of expressions of political, social, cultural, and economic imagination of education and development is at the core of this collective work.